2010
DOI: 10.1097/ftd.0b013e3181dda52a
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Prenatal Alcohol Exposure in Montevideo Uruguay As Determined by Meconium Analysis

Abstract: Prenatal alcohol exposure can lead to a wide range of deficits known as fetal alcohol spectrum disorder. Epidemiologic studies regarding alcohol consumption in pregnancy have concentrated on North America, but recent reports have suggested that consumption is significant in many parts of the world. In Uruguay, alcohol consumption has changed into more risky and dangerous patterns and thus has a theoretical risk of having a high rate of prenatal alcohol exposure. This study characterizes the incidence of prenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
1
28
0
3
Order By: Relevance
“…In relation to EtG, different cut-offs have been proposed (30 and 50 ng/mg) to disclosing intrauterine exposure to ethanol but EtG lacks a universally established cut-off value at the present time [10][11][12]. However, the degree of agreement between detection of ethanol metabolites in neonatal meconium and maternal self-reported ethanol intake during pregnancy remains unclear [4][5][6][7][8][9][13][14][15][16][17][18][19]. It has been shown that reliance on maternal self-reporting is associated with a high probability of error, with substantial underreporting [14,18,20,21].…”
Section: Introductionmentioning
confidence: 98%
“…In relation to EtG, different cut-offs have been proposed (30 and 50 ng/mg) to disclosing intrauterine exposure to ethanol but EtG lacks a universally established cut-off value at the present time [10][11][12]. However, the degree of agreement between detection of ethanol metabolites in neonatal meconium and maternal self-reported ethanol intake during pregnancy remains unclear [4][5][6][7][8][9][13][14][15][16][17][18][19]. It has been shown that reliance on maternal self-reporting is associated with a high probability of error, with substantial underreporting [14,18,20,21].…”
Section: Introductionmentioning
confidence: 98%
“…In the same year, Garcia-Algar et al highlighted 45% ethanol use during pregnancy in a low socioeconomic status cohort from Barcelona (Spain). Similarly, Hutson et al [93] studied the prenatal alcohol exposure in Montevideo (Uruguay). Forty-four percent of meconium samples were above the positive cut-off for FAEEs and represent the newborns with risky prenatal exposure during the final two trimesters of pregnancy [93].…”
Section: Use Of Faees For Diagnosis Prenatal Exposure To Ethanolmentioning
confidence: 97%
“…Similarly, Hutson et al [93] studied the prenatal alcohol exposure in Montevideo (Uruguay). Forty-four percent of meconium samples were above the positive cut-off for FAEEs and represent the newborns with risky prenatal exposure during the final two trimesters of pregnancy [93]. Another study on a cohort from South America was done by Roehsig et al [94].…”
Section: Use Of Faees For Diagnosis Prenatal Exposure To Ethanolmentioning
confidence: 97%
“…Higher rates of drinking during pregnancy have been found in South Africa (20%) and Australia (35%; Giglia & Binns, 2007;Vythilingum, Roos, Faure, Geerts, & Stein, 2012). In certain populations of European (Ireland, Russia, and Spain) and Latin-American (Uruguay) countries, studies indicate that approximately 50% of women drink alcoholic beverages while pregnant (Donnelly et al, 2008;Garcia-Algar et al, 2008;Hutson, Magri, Gareri, & Koren, 2010;Kristjanson, Wilsnack, Zvartau, Tsoy, & Novikov, 2007). A significant number of women drink before knowing they are pregnant and then stop (Alvik, Heyerdahl, Haldorsen, & Lindemann, 2006;Ethen et al, 2009;Floyd, Decoufle, & Hungerford, 1999).…”
Section: Introductionmentioning
confidence: 92%